Evidence Based Pathyapthya in Jalodara/Hepatic Cirrhosis Complicated by Ascites- A Narrative Review (International Journal of Ayurveda and Pharma Research, 2022)
Jalodara is one type of Udararoga. Udararoga is included among Ashtaumahagada by Acharya Charaka which denotes its critical prognosis. The accumulation of fluid in peritoneal cavity is termed as Ascities. Cirrhosis clinical manifestations presents as a much later which makes it difficult to trace in the initial stage. Nearly 30% to 40% of cases are only discovered during autopsy, indicating that in extensive proportion of people, the disease goes undetected during life. The Ayurvedic management of Jalodara mainly focuses upon correcting Agni, Sroto Shodhana and most important being the maintenance of through a strictly followed Pathyapathya. Classical texts suggest a general guidance of salt, water and fat restricted diet with milk as primary source of nutrition initial 3 months to 6 months of treatment. Choice of milk has been Camel milk which is explained in Charaka Samhita which acts both as Ahara and Aushadha. Here, an attempt is made to find out evidence based Pathyapathya (diet regimen) which is effective in the management of Jalodara/hepatic cirrhosis complicated by ascites. Previous studies and research papers are analyzed and also data from P. D. Patel Ayurveda Hospital is collected and inferred. The data reveals that diet comprising of Masur dal soup, Ksheeravritti (milk diet) followed by Camel milk or Cow milk, along the lines of Ayurvedic principles will yield good result.